Legal Clinics in Ukraine: from Legal Education to Legal Practice - Lodzhuk, Maksym; Лоджук, Максим Тарасович (Odesa : Feniks, 2016)
This monograph deals with functioning of legal clinics in Ukraine, their place in the training process of lawyers and their role in the national system of free legal aid. This is a book for scholars and students of higher educational establishments of law and for those who are interested in legal clinics and their activities in Ukraine.
monograph
Lodzhuk M. Legal Clinics in Ukraine: from Legal Education to Legal Practice : monograph / Lodzhuk Maksym. – Оdesa : Feniks, 2016. – 98 p.
Keywords: legal clinics; Ukraine; legal education; professional training of law students; status of legal clinics; clinical legal education; forms of legal aids; free legal aid; професійна підготовка студента-правника; юридична клініка; статус юридичної клініки; юридична клінічна освіта; форми правової допомоги; безоплатна правова допомога; профессиональная подготовка студента-юриста; юридическая клиника; статус юридической клиники; юридическое клиническое образование; формы правовой помощи; бесплатная правовая помощь; legal practice; юридическая практика; юридична практика